Traveling to Tondo : a tale of the Nkundo of Zaire - Aardema, Verna; Hillenbrand, Will (New York : Knopf, 1991)
On his way to his wedding, with his friends as attendants, a civet cat meets with extraordinary and unexpected delays.
Wilson's Children.
School Library Journal starred.
Book Links (A.L.A.).
4.5
K-3
Keywords: Folklore -- Zaire; Folklore -- Zaire; Folklore -- Zaire; Zaire